Predicting factors of cognitive progression in preclinical AD: A five‐year follow‐up of the insight‐study: Neuroimaging: Neuroimaging predictors of cognitive decline. (7th December 2020) - Bombois, Stephanie; Villain, Nicolas; Genthon, Remy; Younsi, Nadjia; Levy, Marcel; Houot, Marion; Colliot, Olivier; Lamari, Foudil; Epelbaum, Stéphane; Habert, Marie‐Odile; Dubois, Bruno
Abstract: Background: As not all the asymptomatic Alzheimer Disease (AD) subjects will progress to symptomatic stages, targeting those individuals at high risk of progression to prodromal AD is relevant, especially for disease‐modifier therapeutic trials. The aim of this study is to determine markers of progression to prodromal AD in cognitively normal individuals. Method: INSIGHT‐preAD study is a cohort of 318 cognitively normal individuals, over 70 years, with subjective memory complaints, followed‐up for 5 years. Subjects were stratified by brain amyloid status (A(+) or A(‐)) according to the uptake of 18F‐Florbetapir. Demographic, cognitive, ApoE status and imaging (MRI and FDG‐PET) were performed at baseline. Clinical and cognitive assessments were repeated every 6 months, MRI, FDG‐PET and amyloid‐PET scans every 2 years. Definition of progressors : MMSE and FCSRT scores below the threshold for inclusion in the study was indicative of a possible progression to prodromal AD. An independent and blinded committee using adjudicated prodromal AD using the IWG‐2 criteria. Statistical analysis : Comparisons between A(+) progressors and A(+) non‐progressors were performed using Wilcoxon test for continuous variables and Fisher's exact tests for qualitative variables. Result: After 5 years, 13 subjects progress to a mild cognitive impairment: 12 prodromal AD (11 typical phenotype; 1 atypical phenotype with a logopenic presentation) and 1 with a Lewy body phenotype. All the progressors were A(+), with a rate of progression of 14% among A(+) individuals. When compared to A(+) non‐progressors, the progressors had lower performance in each FCRST sub‐scores, lower total hippocampal volume (Median [Q1, Q3]: 2.43 [2.24, 2.56] versus 2.65 [2.45, 2.87]) and higher AV45 SUVr (1.23 [0.99, 1.32] versus 0.95 [0.84, 1.10], for a threshold of 0.79). Conclusion: As expected, the predicting factors from cognitively normal individuals to prodromal AD are the co‐occurrence of amyloid burden and tau pathology (represented by hippocampal volume loss and memory deficit). However, only 14% of A(+) subjects progress to prodromal AD after 5 years follow‐up. This result suggests protective and compensatory mechanisms that should be investigated to open up to innovative treatment.